2021
DOI: 10.37332/2309-1533.2021.1-2.20
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm of economic and mathematical model of rating of educational institutions

Abstract: Purpose. The aim of the article is the development of a mathematical model that can be used to determine the ranking of the best educational institutions in the region and systematize educational institutions into appropriate clusters, taking into account their industry significance, ownership, efficiency of public funding and own revenues that effectively use innovation and research potential. Methods of research. The methodological and theoretical basis of the study was the theories and views presented in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Next, the calculation of the second component, namely the indicator of the innovative potential of a scientific and educational institution from the production of innovations, was made based on the classification of educational institutions by the level of efficiency and volume of property, to assess the implementation of innovative potential [29].…”
Section: Materials and Methods Of Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, the calculation of the second component, namely the indicator of the innovative potential of a scientific and educational institution from the production of innovations, was made based on the classification of educational institutions by the level of efficiency and volume of property, to assess the implementation of innovative potential [29].…”
Section: Materials and Methods Of Researchmentioning
confidence: 99%
“…The classification was carried out on the basis of the methodology [29], where it is indicated that for each scientific and educational institution n, the innovative potential of the scientific and educational institution from the production of innovations PN n is determined on the basis of indicators of the volume of income of the special fund Dsf n and the volume of expenses of the budgetary institution V n . Formula for calculation: PN n =Dsf n /V n .…”
Section: Materials and Methods Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the calculation of the indicator of the innovative potential of a research and educational institution from the implementation of innovations based on the classification of educational insti tutions by level of efficiency and amount of property, to assess the implementation of innovation potential was conducted [28].…”
Section: The Indicator Of Innovative Potential Of a Scientific And Ed...mentioning
confidence: 99%
“…The classification is based on the method [28], which states that for each research and educational institution n innovation potential of the research and educational institution from in novation PN n is determined based on the revenue of the special fund Dsf n and expenditures of the budget institution V n . Formula for calculation:…”
Section: The Indicator Of Innovative Potential Of a Scientific And Ed...mentioning
confidence: 99%